Maintenance Therapies for Non-Small Cell Lung Cancer - Blais, Normand; Kassouf, Elie (Frontiers in Oncology, 2014)
Treatment of lung cancer had evolved during the last decade with the introduction of new chemotherapeutic regimens and targeted therapies. However, the maximum benefit reached after first line therapy is limited by the cumulative toxicity of platinum drugs and the subsequent deterioration in performance status in a high percentage of patients who end up receiving not more than one line of treatment. Maintenance therapy had been introduced and evaluated in many large randomized trials showing a delay in tumour progression and an improvement in overall survival. This effective strategy should be taken into account when discussing the initial treatment plan and tailored according to the preferences of both patients and physicians.